Annotated Barriers to Peritoneal and Home Hemodialysis in the U.S. - Thomas A. Golper (Kidney and Dialysis, 2025)
In the last decade, barriers to the growth and utilization of home dialysis have been described in mainstream and significant Nephrology journals. Since then, the suggested solutions have received little attention or have proven ineffective. This situation is even more significant because, in 2019, President Trump issued an executive order to increase the utilization of home dialysis and transplantation. The reasons for failing to achieve the stated goals of the executive order are numerous and can be attributed to barriers at many levels in the health care system. Some of the barriers are unique to the United States and learning from foreign systems would be beneficial. This correspondence attempts to describe and annotate these barriers. I classify them such that local institutions can identify and prioritize solutions. Home dialysis growth can only occur with all stakeholders committing to that end.